Philip Ricard Fendall papers - Fendall, Philip Ricard, 1794-1868.
Professional and family correspondence, receipts, lists, and other papers relating to Fendall's activities on behalf of the Whig Party and William Henry Harrison and Zachary Taylor, his opposition to Andrew Jackson and Martin Van Buren, his work as an editor (under the auspices of the Library of Congress) of the Letters and Other Writings of James Madison (4 volumes; 1865), and his legal career in Alexandria, Va., and as U.S. district attorney for the District of Columbia (1841-1845, 1849-1853). Correspondents include Albert Gallatin Brown, Joseph Henry, Edmund J. Lee, Benjamin Ogle Tayloe, and George Watterston.
Lawyer, editor, and public official. Editor, under the auspices of the Library of Congress, of the Letters and Other Writings of James Madison (4 volumes; 1865).
Collection material in English.
Collection related to the Library of Congress Archives.
Keywords: Brown, Albert Gallatin, -- 1813-1880 -- Correspondence; Harrison, William Henry, -- 1773-1841.; Henry, Joseph, -- 1797-1878 -- Correspondence; Jackson, Andrew, -- 1767-1845.; Lee, Edmund Jennings, -- 1797-1877 -- Correspondence; Madison, James, -- 1751-1836.; Tayloe, Benjamin Ogle, -- 1796-1868 -- Correspondence; Taylor, Zachary, -- 1784-1850.; Van Buren, Martin, -- 1782-1862.; Watterston, George, -- 1783-1854 -- Correspondence; Library of Congress; Whig Party (U.S.); Practice of law -- Virginia -- Alexandria; Public prosecutors -- Washington (D.C.); United States -- Politics and government -- 19th century; Editors; Lawyers; Public officials